2019
DOI: 10.3341/kjo.2018.0013
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Brow Position Changes with Age in Koreans

Abstract: PurposeSeveral studies have described age-associated brow drooping in Westerners. However, there are few studies that address brow drooping in the Asian population, and especially in the Korean population. Therefore, we studied brow position changes with age in Korean individuals.MethodsA total of 300 adults older than 18 years were enrolled. The ImageJ program was used to analyze digital photos of the patients by measuring the following parameters: marginal reflex distance-1, brow-to-pupil distance, nasal ala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…According to previous studies, ImageJ has been measured for posture assessment, wheelchair sitting posture, and brow position measurements. [16][17][18] To measure the degree of sagittal spinal postural alignment, the craniovertebral angle in supine (CVAS) and craniohorizontal angle in supine (CHAS) biomarkers were calculated from the images acquired in ImageJ. Previous studies have reported that standing CVA is an index of the anterior tilt of the head, and standing CHA reflects the position and visual field of the upper cervical spine that are associated with good intra-and interrater reliability in standing measurements ( Figure 2).…”
Section: Measurement Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to previous studies, ImageJ has been measured for posture assessment, wheelchair sitting posture, and brow position measurements. [16][17][18] To measure the degree of sagittal spinal postural alignment, the craniovertebral angle in supine (CVAS) and craniohorizontal angle in supine (CHAS) biomarkers were calculated from the images acquired in ImageJ. Previous studies have reported that standing CVA is an index of the anterior tilt of the head, and standing CHA reflects the position and visual field of the upper cervical spine that are associated with good intra-and interrater reliability in standing measurements ( Figure 2).…”
Section: Measurement Methodsmentioning
confidence: 99%
“…According to previous studies, ImageJ has been measured for posture assessment, wheelchair sitting posture, and brow position measurements. 16 18…”
Section: Methodsmentioning
confidence: 99%
“…The images were captured on a PC, and two angles were calculated for ADS screening using ImageJ (version 1.52, National Institutes of Health, Bethesda, MD, USA). According to previous studies, ImageJ has been used for posture assessment, wheelchair sitting posture, and brow position measurements [18][19][20]. Landmarks for ADS screening were placed on both the lateral canthus and trapezius muscles using the ImageJ point tool.…”
Section: Coronal Spinal Postural Alignment Measurement Using Digital mentioning
confidence: 99%